Acute Sodium Arsenite-Induced hematological and biochemical changes in Wistar Rats: Protective effects of ethanol extract of Ageratum conyzoides (2016)
Background: Ageratum conyzoides L. (Asteraceae) is an annual herbaceous plant used in folklore medicine for the treatment of a wide range of diseases. Objective: To investigate the protective effect of the ethanol leaf extract of A. conyzoides (EEAC) against hematological, serum biochemical and histological alterations induced by Sodium arsenite administration to Wistar rats. Materials and Methods: Twenty male Wistar rats were randomly assigned into four groups of five rats each. Group I received propylene glycol and Group II rats were given the (EEAC, 100 mg/kg b.w.) orally for 7 days. Group III were given a single oral dose of sodium arsenite (NaAsO2 , 2.5 mg/kg b.w.). Animals in Group IV were pretreated with 100 mg/kg EEAC for 7 days followed by a single oral dose of sodium arsenite. Results: Arsenic exposure resulted in significant reductions (P < 0.05) in values of packed cell volume (PCV), hemoglobin concentration (Hb) and red blood cell (RBC) count, and elevation in total white blood cell (WBC) count with insignificant reductions in serum total protein, albumin, and globulin levels. Alterations in aspartate aminotransferase, alanine transferase, alkaline phosphatase, and gamma glutamyl transferase activities, as well as in serum levels of urea, creatinine, glucose, cholesterol, and triglyceride levels, were not statistically significant. EEAC significantly restored (P < 0.05) the PCV, Hb, RBC, and WBC as well as serum albumin, globulin, and total protein to normal values. Conclusion: The results of this study indicate that EEAC possess strong potentials to protect against toxicities induced by sodium arsenite.